2006
DOI: 10.1002/ps.1270
|View full text |Cite
|
Sign up to set email alerts
|

Genetics and evidence for an esterase‐associated mechanism of resistance to indoxacarb in a field population of diamondback moth (Lepidoptera: Plutellidae)

Abstract: Bioassays (at generation G2) with a newly collected field population (designated CH3) of Plutella xylostella L. from farmers' fields in the Cameron Highlands, Malaysia, indicated resistance ratios of 813-, 79-, 171-, 498- and 1285-fold for indoxacarb, fipronil, spinosad, deltamethrin and Bacillus thuringiensis toxin Cry1Ac respectively compared with a laboratory susceptible population (Lab-UK). At G2 the field-derived population was divided into two subpopulations: one was selected (G2 to G7) with indoxacarb (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
82
2
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 132 publications
(92 citation statements)
references
References 27 publications
6
82
2
2
Order By: Relevance
“…Esterases are frequently implicated in the resistance of insects to organophosphates, carbamates, and pyrethroids (Hemingway andRanson 2000, Srigiriraju et al 2009). In a previous study, the resistances to organophosphate and indoxacarb pesticides were found to be positively correlated with an increase in esterase activity (Doichuanngam and Thornhill 1989;Sayyed and Wright 2006), which is congruent with our study. It has also been reported that an abamectinresistant strain of P. xylostella had notably enhanced MFO activity (Qian et al 2008).…”
Section: Pesticide Resistance and Enzyme Activitysupporting
confidence: 93%
“…Esterases are frequently implicated in the resistance of insects to organophosphates, carbamates, and pyrethroids (Hemingway andRanson 2000, Srigiriraju et al 2009). In a previous study, the resistances to organophosphate and indoxacarb pesticides were found to be positively correlated with an increase in esterase activity (Doichuanngam and Thornhill 1989;Sayyed and Wright 2006), which is congruent with our study. It has also been reported that an abamectinresistant strain of P. xylostella had notably enhanced MFO activity (Qian et al 2008).…”
Section: Pesticide Resistance and Enzyme Activitysupporting
confidence: 93%
“…The heritability of chlorfenapyr resistance estimated here was higher than those observed with flubendiamide (h 2 = 0.15) (YAN et al, 2014), chlorantraniliprole (h 2 = 0.26) (GONG et al, 2014), spinosad (h 2 = 0.02) (SAYYED; WRIGHT, 2006), indoxacarb (h 2 = 0.40) (NEHARE et al, 2010) and Bacillus thuringiensis subsp. kurstaki (h 2 = 0.19) and Bacillus thuringiensis subsp.…”
Section: Resultscontrasting
confidence: 54%
“…The short generation time, high fecundity and broad host usage within Brassicaceae as well as its remarkable ability to rapidly evolve insecticide resistance are among these factors (TALEKAR; SHELTON, 1993;SAYYED et al, 2008). Several field populations of P. xylostella have evolved resistance to novel insecticides including chlorantraniliprole (RIBEIRO et al, 2014), spinosad (SAYYED; WRIGHT, 2006) and indoxacarb (NEHARE et al, 2010). Nearly two decades ago, the annual cost of controlling P. xylostella on a worldwide basis was estimated to be US$ 1 billion.…”
Section: Introductionmentioning
confidence: 99%
“…The Bezerros County population still exhibited moderate and high resistance to indoxacarb and abamectin, respectively. The moderate level of resistance (RR = 25.3 times) to indoxacarb was lower than that observed by Sayyed & Wright (2006) in the Cameron Highlands, Malaysia. The resistance to indoxacarb in Bezerros population is possibly associated with its frequent use, despite the rotation usually adopted with methomyl-and B. thuringiensis-based products.…”
Section: Discussioncontrasting
confidence: 57%